PENGEMBANGAN ETIKA SUBSISTENSI BERWAWASAN EKOLOGIS UNTUK PENGEMBANGAN PERILAKU PRODUKTIF BAGI KOMUNITAS PETANI - Imam Santosa; Suyono Suyono (Agritech: Jurnal Fakultas Pertanian Universitas Muhammadiyah Purwokerto, 2018)
The spreading of spatial-ecological conflicts are becoming worse with the greater crisis of ecological values. Natural resource exploitation are becoming more massive by various groups in society. The subsistence ethics of peasants in conducting productive behavior in the countryside is very necessary to be considered in preparing a new formulation of development.  This research uses a qualitative approach to find the new concept. This research is located in District Karangreja and District Bojongsari, Purbalingga Regency. Based on this research, it is revealed that (1) the ecological social condition behind the ecological crisis is that the peasants are aware that their land is vulnerable to erosion but the control measures are still minimal due to the demands of economic factors (achievement of production targets), (2) ecological degradation always coincident with the decline of subsistence ethics, (3) the embryo of the concept of subsistence ethics with ecological insight for the development of productive behavior derived from several ecological values and it still maintained by the peasants who have refrained from excessive use of ground water for interest of irrigation water. Based on this research, it is suggested that the government through the related apparatus should provide more assertive signs so that the fulfillment of production targets (economic orientation) does not ignore the ecological degradation that can cause the leveling off in the future. It is important to realize that the cause of ecological degradation is not a single impact that is going to happen. Therefore, the effort to control this should necessarily require cohesiveness and culture-based peasants.